2018
DOI: 10.1002/hipo.22829
|View full text |Cite
|
Sign up to set email alerts
|

The medial temporal lobe functional connectivity patterns associated with forming different mental representations

Abstract: The medial temporal lobes (MTL), and more specifically the hippocampus, are critical for forming mental representations of past experiences-autobiographical memories-and for forming other "nonexperienced" types of mental representations, such as imagined scenarios. How the MTL coordinate with other brain areas to create these different types of representations is not well understood. To address this issue, we performed a task-based functional connectivity analysis on a previously published dataset in which fMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 71 publications
3
12
0
Order By: Relevance
“…Sheldon and Levine (2018) recently reported results that align well with the above account. Briefly, in this study, participants were tasked with creating mental representations under conditions of autobiographical retrieval, generating a spatial framework, or relating conceptual/perceptual features of objects.…”
Section: How Does An Understanding Of Cortico-hippocampal Network Ilsupporting
confidence: 88%
“…Sheldon and Levine (2018) recently reported results that align well with the above account. Briefly, in this study, participants were tasked with creating mental representations under conditions of autobiographical retrieval, generating a spatial framework, or relating conceptual/perceptual features of objects.…”
Section: How Does An Understanding Of Cortico-hippocampal Network Ilsupporting
confidence: 88%
“…The supramarginal gyrus is not part of the limbic system like the other structures showing significant decreases in DTI values. However, the supramarginal gyrus is located in the parietal lobe which is adjacent to the temporal lobe 21 . With extension of the sclerotic structure beyond the temporal lobe in the pathologic hemisphere into surrounding areas, the supramarginal gyrus may be affected, as in this case, Additionally, as neuronal connections traverse the brain to reach the mesial temporal lobe, fibers may cross through or near the supramarginal gyrus as well leading to the significant decrease in the DTT versus the DTI value on the diseased side.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the important evidence supporting a posterior–anterior organization of episodic retrieval processes come from task fMRI studies (Lacot et al, 2017; Mugikura et al, 2016; Ritchey et al, 2015; Ritchey, Wang, Yonelinas, & Ranganath, 2019; Rosenbaum, Ziegler, Winocur, Grady, & Moscovitch, 2004; Sheldon & Levine, 2018). In examining functional activation in the MTL cortex during source and item memory trials, a classic fMRI study conducted by Davachi, Mitchell, and Wagner (2003), observed that activity in the PRC during encoding predicted subsequent item recognition, but not source retrieval.…”
Section: Introductionmentioning
confidence: 99%
“…While evidence from task and resting‐state fMRI studies supporting the posterior–anterior division of labor in the MTL is plentiful (Epstein, Harris, Stanley, & Kanwisher, 1999; Maass et al, 2015; Murray et al, 2007; Nadel et al, 2012; Olsen & Robin, 2020; Ritchey et al, 2015; Ryan et al, 2012; Sheldon & Levine, 2018; Staresina et al, 2011), there is little support from structural MRI studies in healthy young adults. Indeed, much of the evidence linking the amount of gray matter (GM) in MTL regions of interest (ROIs) with their proposed functions has been collected from studies in aging or clinical populations (Bohbot et al, 2015; Kivisaari, Tyler, Monsch, & Taylor, 2012; Olsen et al, 2013; Olsen et al, 2017; Palombo et al, 2013;Yeung et al, 2017; Yeung et al, 2019).…”
Section: Introductionmentioning
confidence: 99%